Annual reports in computational chemistry. - Spellmeyer, David Charles, 1961- (Annual reports in computational chemistry, 2006)
Section headings in this work are: 'Chemical Education'; 'Quantum Mechanical Methods'; 'Molecular Modeling Methods'; 'Advances in QSAR/QSPR'; and 'Applications of Computational Methods'.